Giant neurons in the macaque pulvinar: a distinct relay subpopulation - Imura, Kosuke; Rockland, Kathleen S. (Frontiers in Neuroanatomy, 2007)
Calbindin positive (CB+) giant neurons are known to occur within the pulvinar nucleus in subhuman primates. Here, we demonstrate by combined retrograde tracing and immunocytochemistry that at least some of these are pulvinocortical relay neurons, and further report several distinctive features. First, in contrast with non-giant relay neurons, the giant neurons are often solitary and isolated from a main projection focus. The question thus arises of whether their cortical projections may be non-reciprocal or otherwise distinctive. Second, these neurons are positive for GluR4; but third, they are otherwise neurochemically heterogeneous, in that about one-third are positive for both parvalbumin (PV) and CB. Presumably, these subpopulations are also functionally heterogeneous. These results provide further evidence for the idea of multiple, interleaved organizations within the pulvinar; and they imply that thalamocortical projections are more disparate than has yet been appreciated. Finally, we found that giant CB+ neurons have a distinctive meshwork of large, PV+ terminations, prominent at the first dendritic branch point. In size and location, these resemble inhibitory terminations from the zona incerta or anterior pretectal nucleus (APT), as recently described in higher order thalamic nuclei in rats. One can speculate that giant neurons in the macaque pulvinar participate in a layer 5-APT-thalamus (giant neuron) extrareticular pathway, functionally distinct from the layer 6-reticular nucleus-thalamus network.